Development of a novel integrated process for co-production of β-galactosidase and ethanol using lactose as substrate. (April 2017) - You, Shengping; Zhang, Jianye; Yin, Qingdian; Qi, Wei; Su, Rongxin; He, Zhimin
Graphical abstract: Highlights: A novel integrated process for co-production of β-galactosidase and ethanol was built. A new mathematic model for a new recycling permeabilization was established. β-Galactosidase product was at 2.61 U/mg and ethanol product was at 33.8% (v/v). The novel integrated process might be a feasible strategy to scale up. Abstract: A novel integrated process was developed successfully for co-production of β-galactosidase and ethanol using lactose as substrate, containing fermentation ( Kluyveromyces lactis ), isolation, permeabilization (a new recycling process) and spray drying. Firstly, a new fed-batch strategy optimized co-produced β-galactosidase at 105.91 U/mL and ethanol at 32.16 mg/mL, 4.40-fold and 10.82-fold increase over the results from initial conditions, respectively. Then a new mathematic model for the recycling permeabilization was established successfully. As expected, the total cells sediment from isolation of the fed-batch culture was permeabilized completely by distilled ethanol from broth supernatant. More amazedly, the specific activity of β-galactosidase product by spray drying the permeabilized cells reached 2.61 U/mg, meeting the demand of commercial products. Furthermore, the ethanol product at 33.8% (v/v) was obtained from the novel integrated process, which could be applied for various applications. To conclude, the novel integrated process might be a feasible strategy to scale up for industrialization.